2013
DOI: 10.1093/geronb/gbt131
|View full text |Cite
|
Sign up to set email alerts
|

Life Expectancy in Long-Term Institutional Care by Marital Status: Multistate Life Table Estimates for Older Finnish Men and Women

Abstract: The resources that are needed to provide long-term care services will increase as age of death increases. We demonstrate significantly longer care expectancy among women and among the unmarried.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 19 publications
4
24
1
Order By: Relevance
“…Lifetable studies estimated likelihoods for Australia, 14,15 USA 23 and UK 24 . Six simulation models were from the US 25–30 and one from Finland 31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifetable studies estimated likelihoods for Australia, 14,15 USA 23 and UK 24 . Six simulation models were from the US 25–30 and one from Finland 31 …”
Section: Resultsmentioning
confidence: 99%
“…24 Six simulation models were from the US [25][26][27][28][29][30] and one from Finland. 31 Median overall estimates of lifetime use of RAC for people aged 65+ varied substantially: 39% (range 22%-47%) for decedent cohorts, 34% (26%-53%) for lifetables and 53% for simulations (35%-60%). Of the 12 studies from the US, decedent cohort studies in general yielded lower estimates than other studies, but there was wide variation, from 35% 26 to 60%.…”
Section: International Comparisonsmentioning
confidence: 98%
“…Broad's study found that the proportion using RAC for late‐life care increased from 47% (aged 65 years) to 66% for persons aged 85 years or more in New Zealand 1 . Other analyses have demonstrated that women are more likely to use residential care than men 2,21 due to increased life expectancy, and the likelihood that they will not have a spouse still living who is able to care for them 7,9 . Different risk factors between genders may also apply.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the expected move and the actual relocation to a nursing home indicates that the development of home‐care arrangements is almost unpredictable. A Finnish study with a population aged 65 and over shows that women aged 65 and over are more likely to go into institutional LTC than men and are also more likely to stay there longer . Unexpected hospital admissions may be a reason for delays in arranging institutional care.…”
Section: Discussionmentioning
confidence: 99%